Tanggung Jawab Organisasi Notaris Terhadap Pelaksanaan Magang Calon Notaris Di Kota Padang - Tatik Kustiati; Azmi Fendri; Rembrandt Rembrandt (Nagari Law Review, 2018)
According to Article 3 letter f of Law Number 2 Year 2014 regarding Amendment to Law Number 30 Year 2004 about Notary Position a Notary candidate should take apprenticeship 24 consecutive months before allowed to practice as a notary. The problem is how the obligation conducted and how is the responsibility notary organization in holding the apprenticeship. The method taken in this research is empirical juridical. The juridical approach is used to analyse the various laws and regulations, while the empirical approach is used to view and analyse the law compare to its practice in society along with all its aspects. Because in this research examining people in relation of life in society, hence method of empirical law research can be regarded as research of sociological law which is branch of law of law (socio legal research in sociological jurisprudence) because legal research is taken from facts that exist in a society. The research was held in Notary organization known as Indonesian Notary Association in Padang . The research show that the Notary organization plays an important role in conducting apprenticeship for notary candidate, by permit their office chosen to hold apprenticeship. The each notary has also provided the notary candidate skill and knowledge that will be very useful for next practice. Each Notary candidate is required to attend the internship as one of the requirements to be able to follow the Notary Code of Ethics Examination which is preceded by Examination of Extraordinary Member in order to be appointed Notary